Rising tiger : [large type] a thriller - Thor, Brad (Thor, Brad. Scot Harvath, 2022)
"An unprecedented, potentially nation-ending threat has materialized on the world stage. Though the United States has long been aware of the growing risk, the clock has now run out. With the stakes higher than they have ever been, it is time to unleash Scot Harvath. As America's top spy, Harvath has the skills and experience necessary to handle any situation, but this assignment feels different and appears doomed from the start. With democracy itself hanging in the balance, Harvath will risk everything to untangle the explosive plot and bring every last bad actor to justice"--